Nutrition of children affected by celiac disease - G. N. Yankina (Бюллетень сибирской медицины)
In the world frequency of patients affected by celiac disease comprises 1 per 184 persons.  The disease is provoked by using gluten contaning products for food. Dietotherapy is the only and effective way to treat children affected by celiac disease. Wheat, rye, barley and oats are excluded from nutrition of children affected by celiac disease. Among cereal products it is allowed to eat corn, rice, buckwheat, millet. For nutrition of children with celiac disease it is recommended to use certified products.